Gross and Histomorphological Study of the Ovary and Oviduct of Turkey Hen with Especial Emphasis on the Sperm-Host Gland - Islam, Mohammad Rafiqul; Hasan, Imam; Monisha, Nure Zannat; Afrin, Marya (The Iraqi Journal of Veterinary Medicine, 2021)
Turkey bird is one of the popular poultry species which is reared primarily for meat production and considered as one of the major sources of animal protein. With such importance of this species, this study was designed to investigate the gross and histomorphology of the ovary and oviduct with especial emphasis on sperm-host glands of the turkey hen involving ten mature female turkeys (Meleagris gallopavo). The present study highlighted the distribution pattern of sperm-host glands (SHGs) in the oviduct of turkey hen that has a potential role in producing a fertile egg in poultry industries. The oviduct of turkey consists of the infundibulum, magnum, isthmus, uterus, and vagina which are sole distributors for making nutrition enriched egg. The tissue samples were collected from the ovary, different segments of the oviduct and especially uterovaginal junction (UVJ) and infundiomagnal junction of the oviduct. The ovaries and the oviducts were dissected and fixed in Bouins solution and processed for a light microscopic study. Histologically, the left ovary of turkey consisted of an outer cortex and inner medulla, with different stages of follicles. In all areas of the oviduct except the infundibulum and vagina, the tunica mucosa epithelium was lined with ciliated pseudo stratified columnar epithelium, and the lamina propria-submucosa contained branched tubular glands. Sperm-storage tubules were observed in the uterovaginal junction and infundibulo-magnum junction. These tubules were mostly branched, slightly coiled and extended into the lamina propria from the bases of the mucosal folds. These glands had proximal and distal parts; the proximal part was lined by pseudostratified columnar epithelium and distal part by non-ciliated simple columnar epithelium. The number of sperm host glands was more at uterovaginal junction than infundibulomagnal junction. The sperm-host glands might play a functional role in the storage and release of spermatozoa from the SHGs in response to oviposition or ovulation. The results would help poultry scientists and farmers in developing effective disease control and growth strategies.